Detection, identification and quantitation of Cryptosporidium parvum in water samples and Ascaris lumbricoides in sludge samples using real-time Polymerase Chain Reaction coupled with the high-resolution melt curve assay - Lombard, Marile (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc)--Stellenbosch University, 2016.